PENGARUH MOTIVASI KERJA, DISIPLIN KERJA DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN DI PT AVAVA DUTA INDONESIA - Handoko (LPPM Universitas Putera Batam, 2025)
In today’s competitive environment, companies must effectively compete, with human resources playing a crucial role. Employees require training and motivation to perform optimally, enhancing the company’s competitiveness and survival. Key factors influencing employee performance include work motivation, discipline, and workload. This study analyzes the impact of incentives, work motivation, and workload on employee performance at PT Avava Duta Indonesia. A quantitative approach with a descriptive design wasused, involving 196 employees as the sample with saturated sampling. Data analysis was conducted using SPSS 25, including validity, reliability, normality, multicollinearity, heteroscedasticity tests, multiple linear regression, coefficient of determination, as well as t-tests and F-tests. The findings reveal that work motivation (significance 0.001), work discipline (significance 0.007), and workload (significance 0.000) all significantly affect employee performance, with values less than 0.05. In conclusion, incentives, work motivation, and workload positively and significantly impact employee performance, both simultaneously and partially.